Sustainable development goals: teachers' vision on conceptualization and accountability (Research, Society and Development, 2022)
This article has as its general objective the Sustainable Development Objectives (SDG), such as the following sustainable development objectives and those according to higher education teachers, considering as a basis two lines of research: analyze and the basic objectives for the alternative objectives to achieve the objectives. The two approaches were transformed into questions, which constituted the methodology of the question, which belongs to the research. The methodology is based on the Research Cycle, a strength in research research, field work and material treatment. Based on the analysis of the responses, a precarious understanding of the SDGs can be seen. The initial hypothesis that the research target audience will expand as it has the potential to expand the SDGs and, with that, greater engagement and adoption of actions to meet these real ones, was not fully extended. The main factor that marked as responses was the lack of a sense of belonging and awareness of responsibility towards the SDGs.